Development of Web Application for Certificate Automation using Cloudflare DNS API and ZeroSSL - Fredian Simanjuntak; Gary Happydinata`; Herman (Universitas Ahmad Dahlan, 2026)
Existing SSL/TLS automation tools were largely server-centric and required host-level configuration. These limitations increased complexity in distributed and multi-domain environments. This study proposed a centralized web-based SSL certificate automation system. The system integrated the Cloudflare DNS API and ZeroSSL REST API for certificate lifecycle management. The research adopted the Agile Scrum methodology during system development. An asynchronous queue-based architecture was implemented to support concurrent certificate issuance. The architecture reduced API rate-limit constraints. Automated Domain Validation (DV) was successfully performed through DNS integration. The system centralized certificate storage and monitoring. The interface simplified administrator operations. Configuration errors were reduced during certificate deployment. Operational efficiency was improved for distributed infrastructures. A usability evaluation was conducted with 25 technical practitioners. The evaluation produced a System Usability Scale mean score of 83.5 with a standard deviation of 6.7. The findings indicated excellent user acceptance and system usability. In conclusion, the proposed system effectively automated SSL certificate management through a centralized and usability-oriented approach. The system also minimized operational overhead and dependency on host-level configuration.